2017
DOI: 10.1016/j.biocon.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

High mammal species turnover in forest patches immersed in biofuel plantations

Abstract: Remnant habitat patches immersed within biofuel cropland matrices can retain considerable species diversity, although the effects of land use change on species persistence in historically modified landscapes remain unclear. The Atlantic Forest is one of the most fragmented South American biodiversity hotspots and retains about 12% of its original vegetation cover. Most of these remnants are distributed in small isolated fragments immersed mainly within pastures and sugarcane monocultures. Here we examine how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 79 publications
8
73
0
16
Order By: Relevance
“…Biodiversity changes in tropical ecosystems are extremely complex to evaluate and understand, as they are scale and context dependent, differ among taxonomic groups and ecosystems, and often respond differently to similar environmental changes (Vellend et al 2013; Dornelas et al 2014; Newbold et al 2015; McGill et al 2015; Boesing et al 2018; Catano et al 2017; Magurran et al 2018). For instance, recent studies found no evidence for systematic loss in local diversity (Vellend et al 2013; Dornelas et al 2014), while several others indicate this is not true for the tropics, where a variety of taxa experienced steep local species decreases in human modified landscapes (Haddad et al 2015; Mendenhall et al 2016; Beca et al 2017; Ceballos et al 2017; Farah et al 2017; Galetti et al 2017; Barlow et al 2018; Bovendorp et al 2018). Whereas the unprecedented level of forest degradation, fragmentation and intensive land use have an undeniable contribution to immediate and long-term local diversity loss (Haddad et al 2015; Barlow et al 2018), less is known regarding how these disturbances modify and drive the community composition along time and space, regardless of the recent growing interest and evidence on these compositional shifts (Dornelas et al 2014; Haddad et al 2015; McGill et al 2015; Collins et al 2017; Olden et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity changes in tropical ecosystems are extremely complex to evaluate and understand, as they are scale and context dependent, differ among taxonomic groups and ecosystems, and often respond differently to similar environmental changes (Vellend et al 2013; Dornelas et al 2014; Newbold et al 2015; McGill et al 2015; Boesing et al 2018; Catano et al 2017; Magurran et al 2018). For instance, recent studies found no evidence for systematic loss in local diversity (Vellend et al 2013; Dornelas et al 2014), while several others indicate this is not true for the tropics, where a variety of taxa experienced steep local species decreases in human modified landscapes (Haddad et al 2015; Mendenhall et al 2016; Beca et al 2017; Ceballos et al 2017; Farah et al 2017; Galetti et al 2017; Barlow et al 2018; Bovendorp et al 2018). Whereas the unprecedented level of forest degradation, fragmentation and intensive land use have an undeniable contribution to immediate and long-term local diversity loss (Haddad et al 2015; Barlow et al 2018), less is known regarding how these disturbances modify and drive the community composition along time and space, regardless of the recent growing interest and evidence on these compositional shifts (Dornelas et al 2014; Haddad et al 2015; McGill et al 2015; Collins et al 2017; Olden et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that secondary forests may play an important role in conservation (Santos et al 2007, Chazdon et al 2009; Dent & Wright 2009; Tabarelli et al 2012), as they hold a depleted but relevant portion of biodiversity even within HMLs. Abundant evidence is available for birds (Karp et al 2012; Emer et al 2018), mammals (Galetti et al 2009; Pardini et al 2010; Beca et al 2017) and plants (Arroyo-Rodríguez et al 2008; Lima et al 2015; Sfair et al 2016; Farah et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Restoration presents an opportunity to increase the range and population size of animal‐dispersed, large‐seeded species, which is particularly important for rare species persisting in human‐modified, defaunated landscapes (Beca et al., ). We highlight the economic limitations and regulation opportunities to better incorporate these high conservation value trees in restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide habitat fragmentation and defaunation challenge the maintenance of species and their ecological functions (Fahrig 2003;Hagen et al 2012;Dirzo et al 2014) with cascading consequences for ecosystem services (Bello et al 2015;Haddad et al 2015). Yet, the remnant patches can surprisingly hold a significant fraction of biodiversity (Morante-Filho et al 2016;Sfair et al 2016;Beca et al 2017). However, the long-term persistence of viable populations requires connectivity among patches (Hanski 1998;Leibold et al 2004), which may crucially depend on the maintenance of functional ecological interactions.…”
Section: Introductionmentioning
confidence: 99%